1998
DOI: 10.1111/j.1600-0447.1998.tb09964.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of obsessive‐compulsive disorder and pathological gambling with Huntington's disease in an Italian pedigree: possible association with Huntington's disease mutation

Abstract: This paper describes a pedigree with Huntington's disease (HD), in which three cases of obsessive-compulsive disorder (OCD) and two cases of pathological gambling (PG) were identified. The mutation analysis of the HD gene was carried out in the examined individuals who were at risk for HD. In fact, OCD and PG only occurred in carriers of the HD expansion. The possible implications of this finding are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…The presence of obsessive and compulsive symptoms (OCs) has been previously documented in patients with HD as less common than other psychiatric symptoms [65,69,70,71,72]. However, a study by Marder et al reported that 22.3% had obsessive and compulsive symptoms at their first clinical visit, suggesting that these symptoms may be more common than previously recognized in this population.…”
Section: Clinical Features In Hd and Psychiatric Disordersmentioning
confidence: 93%
See 1 more Smart Citation
“…The presence of obsessive and compulsive symptoms (OCs) has been previously documented in patients with HD as less common than other psychiatric symptoms [65,69,70,71,72]. However, a study by Marder et al reported that 22.3% had obsessive and compulsive symptoms at their first clinical visit, suggesting that these symptoms may be more common than previously recognized in this population.…”
Section: Clinical Features In Hd and Psychiatric Disordersmentioning
confidence: 93%
“…They were found to be particularly important in an advanced stage of the disease. Those patients with an early age at onset of HD seem to be at an increased risk of psychoses [71]. A very low prevalence should be explained by a frequently use of neuroleptics [29].…”
Section: Clinical Features In Hd and Psychiatric Disordersmentioning
confidence: 99%
“…De Marchi et al [69] reported on a family with HD, and a strong association between OCD and pathologic gambling. The lifetime prevalence of OCD in the extended family was 34% for biologically related persons, the majority of whom had HD or were at 50% risk.…”
Section: Comments and Outcome On Target Symptomsmentioning
confidence: 98%
“…It is noteworthy that patient 1 had suffered from OCD in the 25 years preceding the onset of her HD (De Marchi et al 1998), and that both cases came from an extended pedigree where an outstandingly high prevalence of OCD syndromes is being detected (manuscript in preparation). It can be argued that some clinical markers, such as the presence of OCD in this instance, might possibly help pinpoint distinct subgroups of HD patients, each with its specific neurotransmitting and neuroanatomical patterns of involvement (De Marchi and Mennella 2000).…”
Section: Discussionmentioning
confidence: 97%